Monitoring Coronavirus Disease 2019: A Review of Available Diagnostic Tools - Liu, Shanshan; Li, Qiuyue; Chu, Xuntao; Zeng, Minxia; Liu, Mingbin; He, Xiaomeng; Zou, Heng; Zheng, Jianghua; Corpe, Christopher; Zhang, Xiaoyan; Xu, Jianqing; Wang, Jin (Frontiers in Public Health, 2021)
Coronavirus Disease 2019 (COVID-19) pneumonia is caused by the virus SARS-CoV-2 and has rapidly become a global public health concern. As the new type of betacoronavirus, SARS-CoV-2 can spread across species and between populations and has a greater risk of transmission than other coronaviruses. To control the spread of SARS-CoV-2, it is vital to have a rapid and effective means of diagnosing asymptomatic SARS CoV-2 positive individuals and patients with COVID-19, an early isolation protocol for infected individuals, and effective treatments for patients with COVID-19 pneumonia. In this review, we will summarize the novel diagnostic tools that are currently available for coronavirus, including imaging examinations and laboratory medicine by next-generation sequencing (NGS), real-time reverse transcriptase–polymerase chain reaction (rRT-PCR) analysis, immunoassay for COVID-19, cytokines and T cells immuno-assays, biochemistry and microbiology laboratory parameters in blood of the patients with COVID-19, and a field-effect transistor based biosensor of COVID-19. Specifically, we will discuss the effective detection rate and assay time for the rRT-PCR analysis of SARS-CoV-2 and the sensitivity and specificity of different antibody detection methods, such as colloidal gold and ELISA using specimen sources obtained from the respiratory tract, peripheral serum or plasma, and other bodily fluids. Such diagnostics will help scientists and clinicians develop appropriate strategies to combat Coronavirus Disease 2019.